Social Knowledge as a Problem of Practice and Theory - Karosas, Justinas (Problemos, 1989)
The specific character of social knowledge is discussed in the paper. Dependence of the knowledge on historical reality is assumed. Proceeding from the assumption, it is argued that ideological and cognitive factors do interweave in the knowledge, making the cognitive measure of the social truth one-sided and requiring an additional value measure. Further it is shown that social theory is constrained to link two opposites, namely, freedom and necessity, what makes the theory logically contradictive and gives rise to the problem of the relation between value and truth. The article concludes with the inference that the problem is of practical origin and can be solved only when material conditions are nature for the elimination of social alienation.